Laboratory of Pedagogical Skills of Prydniprovska State Academy of Civil Engineering and Architecture: On the Way from Traditional Methods to Modern Educational Online Technologies - Galyna YEVSEIEVA; Galyna LYSENKO; Svitlana VOLKOVA (Communications of International Proceedings, 2021)
Realizing the importance of continuous self-development and self-improvement of research and teaching staff in order to increase the level of their professional and pedagogical competence, it was decided to create the Laboratory of Pedagogical Skills (LPS), which has an ambitious goal to become a school for professional competence of teachers of Prydniprovska State Academy of Civil Engineering and Architecture (PSACEA), Dnipro, Ukraine. The purpose of the article is to prove the positive impact of the Laboratory of Pedagogical Skills on raising of the professional level of PSACEA teachers, as well as to justify the feasibility of transferring its activities into an online format. As a result of the analysis it was found that during 2014-2019 the Laboratory of Pedagogical Skills of PSACEA initiated a number of scientific and pedagogical activities that contributed to the professional and pedagogical growth of teachers of the Academy, establishing close cooperation with representatives of the teaching community of other higher education institutions of Dnipro city. The introduction of quarantine diversified the work of the Laboratory, which currently contributes to improving not only scientific, pedagogical, teaching and methodological competencies of teachers, but also to increase their professional competence in the use of information technologies in education. Today the virtual Laboratory of Pedagogical Skills of PSACEA carries out permanent monitoring of professional growth of teachers of the Academy, organizes network interaction with all departments on revealing of needs and inquiries of scientific and pedagogical workers, promotes creation of humanitarian space in technical institution of higher education.
Keywords: Laboratory of pedagogical skills; research and teaching staff; professional and pedagogical competence; information technologies in education; humanitarian space in technical institution of higher education